Relative impact of human harvest and wolf predation on two ungulate species in Central Italy. Issue 4 (13th May 2020) - Bassi, Elena; Gazzola, Andrea; Bongi, Paolo; Scandura, Massimo; Apollonio, Marco
Abstract: Data collected from 2000 to 2010 on a predator–prey system in eastern Tuscany (central Italy) were used to investigate the relative impact of human harvest and natural predation by wolves ( Canis lupus ) on the local populations of their main prey: wild boar ( Sus scrofa ) and roe deer ( Capreolus capreolus ). We estimated the percent composition of wolf diet from scat analysis ( n = 2, 150) and converted it into ingested biomass and number of killed individuals by quantifying the energy requirement of the resident wolf pack based on the field metabolic rate formula. Moreover, we collected data on hunting bags, and investigating the age/weight class preferences of both wolves and hunters compared their impacts on the two ungulate populations. In both prey species, losses due to hunting resulted to be eight to nine times higher than those due to wolf predation. In terms of number of individuals removed per year, the wild boar was the main prey species for wolves (mean ± SD : 83 ± 23) and the most harvested by hunters (mean ± SD : 609 ± 241). Wolves targeted the intermediate weight class (10–35 kg) in wild boar and showed no preference for a specific class of roe deer, while hunters targeted the largest classes in both species. The combined removal by hunters and wolf predation did not exceed the recruitment of both ungulate populations. We can therefore argue that a top‐down force is unlikely to contrast the population growth of the two ungulate species in Central Italy. Abstract : We used 10 years data to investigate the relative impact of human harvest and predation by wolves on the local populations of wild boar and roe deer. Wolf diet was estimated from scat analysis and the energy requirement of the resident wolf pack was quantified on the basis of the field metabolic rate formula; then, we collected data on hunting bags. Our results showed that the combined removal by the two predators did not exceed the recruitment of ungulate populations, suggesting a bottom‐up force is acting on the two ungulate species.